C‐Abl tyrosine kinase regulates neutrophil crawling behavior under fluid shear stress via Rac/PAK/LIMK/cofilin signaling axis. Issue 3 (20th November 2017) - Tong, Haibin; Qi, Dake; Guan, Xingang; Jiang, Guiquan; Liao, Zhiyong; Zhang, Xu; Chen, Peichao; Li, Nan; Wu, Mingjiang
Abstract: The excessive recruitment and improper activation of polymorphonuclear neutrophils (PMNs) often induces serious injury of host tissues, leading to inflammatory disorders. Therefore, to understand the molecular mechanism on neutrophil recruitment possesses essential pathological and physiological importance. In this study, we found that physiological shear stress induces c‐Abl kinase activation in neutrophils, and c‐Abl kinase inhibitor impaired neutrophil crawling behavior on ICAM‐1. We further identified Vav1 was a downstream effector phosphorylated at Y174 and Y267. Once activated, c‐Abl kinase regulated the activity of Vav1, which further affected Rac1/PAK1/LIMK1/cofilin signaling pathway. Here, we demonstrate a novel signaling function and critical role of c‐Abl kinase during neutrophil crawling under physiological shear by regulating Vav1. These findings provide a promising treatment strategy for inflammation‐related disease by inactivation of c‐Abl kinase to restrict neutrophil recruitment. Abstract : We demonstrate a critical signaling function of c‐Abl kinase in neutrophil crawling under physiological shear by regulating Vav1 activity and Rac/PAK/LIMK/cofilin signaling axis. These findings provide the feasibility for targeting c‐Abl kinase to restrict the recruitment of neutrophils for the amelioration of inflammation‐related disease.